Managerial economics : applications, strategy, and tactics - McGuigan, James R.; Moyer, R. Charles; Harris, Frederick H. Deb. (Cincinnati, OH : South-Western College, 1999)
This book is divided into five parts: Introduction to managerial decision making; Demand and forcasting; Production and cost; Pricing and output decisions: Strategy and tactics; Long-Term investment decisions and risk management.
Keywords: Economics; Managerial economics; Managerial economics; Managerial economics -- Problems, exercises, etc